Sistem Pendukung Keputusan Penerima Beasiswa Dengan Metode Fuzzy Logic (Studi Kasus: STT Sumatera) - Sartana; Simbolon, Fauzi Haris; Simbolon, Ratna Wati (LOFIAN: Jurnal Teknologi Informasi dan Komunikasi, 2023)
Sumatra Theological College (STT) is one of the educational institutions that provides scholarships to students every year. This is of course with the aim to ease the burden of student education costs. At the beginning of each semester of the new school year, STT Sumatra selects students who are eligible for scholarships. This selection process requires accuracy and time, because student data will be compared with the scholarship criteria one by one. The purpose of this scholarship is to help students obtain proper educational services in tertiary institutions. Selection of scholarship recipients is carried out by a scholarship selection committee. The process of determining scholarship recipients goes through several stages and uses conventional methods. Several problems were found including the long time in the process of selecting scholarships for the underprivileged, difficulties in determining scholarship recipients. .So we need an application that can help determine scholarship recipients. Then a decision support application for determining underprivileged scholarship recipients was designed. The aim is to assist the decision-making process in determining scholarship recipients. This decision support application for scholarship recipients uses the Fuzzy Logic method as a method that will process the results of student assessments which will produce a ranking from the largest to the smallest, with this method decision making becomes easier.